2010
DOI: 10.1016/j.jcmg.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Plaque Characterization by CT Angiography and Post-Procedural Myocardial Infarction in Patients With Elective Stent Implantation

Abstract: Post-procedural myocardial injury was associated with the volume and fraction of LAP as detected by MDCT. The volume of LAP was an independent predictor of positive TnT. Plaque analysis by MDCT would be a useful method for predicting post-procedural myocardial injury after percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 38 publications
2
45
1
1
Order By: Relevance
“…This pathophysiologic mechanism is supported by direct observations documenting lipid debris in fatal cases of distal embolization 26 and by recent findings obtained with various techniques, including NIRS, that the extent of lipid core in the vessel wall is diminished after balloon inflation. 17,18,36,37 The present study demonstrates a high relative risk of periprocedural MI in lesions with a maxLCBI 4 mm Ն500, a quantitative measure determined on-line by the NIRS system that does not require subjective operator interpretation or postprocedure analysis.…”
Section: Intracoronary Imaging and Lcpmentioning
confidence: 62%
“…This pathophysiologic mechanism is supported by direct observations documenting lipid debris in fatal cases of distal embolization 26 and by recent findings obtained with various techniques, including NIRS, that the extent of lipid core in the vessel wall is diminished after balloon inflation. 17,18,36,37 The present study demonstrates a high relative risk of periprocedural MI in lesions with a maxLCBI 4 mm Ն500, a quantitative measure determined on-line by the NIRS system that does not require subjective operator interpretation or postprocedure analysis.…”
Section: Intracoronary Imaging and Lcpmentioning
confidence: 62%
“…24 We 36 Uetani et al demonstrated that PMI was associated with the volume and fraction of LAP by MDCT. 37 We demonstrated that a CT attenuation value <55 Hounsfield units, PR (remodeling index >1.05) and spotty calcification were significant predictors of PMI; the presence of all 3 CT characteristics showed a high PPV of 94%, and their absence showed a high NPV of 90%. 38 Kodama et al demonstrated that CCTA-verified circumferential plaque calcification with LAP and PR were determinants of slowflow phenomenon during PCI.…”
Section: Assessment Of Coronary Vulnerable Plaquementioning
confidence: 71%
“…15, 24 Recently, we have reported that coronary plaque with a large LDP volume is related to post-procedural myocardial infarction in elective PCI cases. 18 A report suggests that the presence of a large LDP volume increases the incidence of a no-reflow phenomenon in patients undergoing PCI. 25 Therefore, much careful attention should be paid to the treatment of coronary plaque with a large LDP volume.…”
Section: Discussionmentioning
confidence: 99%
“…Using Color Code Plaque™ (GE Healthcare), as previously reported, 17 the volume of each component of coronary plaque within the ROI was measured automatically, based on the stratified CT density. As previously reported, 18 each plaque component and lumen (filled with contrast medium) were defined as follows: (1) low-density (~50 Hounsfield units [HU]); (2) moderate-density (50-150 HU); (3) lumen (150-500 HU); (4) high-density (500 HU~). The total plaque volume (TPV) [sum of volume of LDP, moderate-density plaque (MDP) and high-density plaque (HDP)] and the fraction of each plaque component, defined as the volume of each component divided by the TPV, were also estimated.…”
Section: Arai K Et Almentioning
confidence: 99%